A Study to Assess the Satisfaction Level of Children on Parent–Child Relationship Among Adolescent Girls Studying at Selected Educational Institutions in Honavar, Uttara Kannada - A. Sagaya Arockia Mary; Wincy Thirumurugan (International Journal of Women's Health Nursing And Practices, 2023)
Background: A strong parent-child relationship (PCR) is essential for a child’s overall development. This study aimed to explore the quality of parent-child relationships, particularly with fathers, among Indian adolescent girls. While societal attitudes have evolved, concerns remained about whether female children receive the same love, respect, and care as their male counterparts. Methodology: This research used a quantitative approach with a descriptive design. A total of 253 adolescent girls from Prabhat Nagar Govt. School, Mar Thoma School, and St. Ignatius Institute of Health Sciences in Honavar were selected using purposive sampling. Data was collected through a five-point rating scale consisting of 10 statements measuring satisfaction with the PCR. Statistical analysis included mean calculations, frequency, percentage distribution, and chi-square tests to identify associations between satisfaction and demographic variables. Results: The overall satisfaction level revealed that none were “very dissatisfied”, 0.39% were “dissatisfied”, 2.7% were “neutral”, 75.09% were “satisfied”, and 21.73% were “very satisfied” with their parent-child relationships. Chi-square tests showed significant associations with various demographic variables, such as age, educational course, religion, area of residence, type of family, number of children, number of siblings, father’s education, mother’s education, father’s occupation, and mother’s occupation, indicating a strong relationship between these factors and satisfaction with the PCR. Conclusion: The study concluded that the majority of adolescent girls in the selected research setting expressed satisfaction with their parent-child relationships and were content with their parents’ attitudes and acceptance. The findings emphasize the importance of fostering positive parent-child relationships for the overall well-being and development of adolescents.
Keywords: Adolescent girls; Assessment; educational institutions; parent–child relationship (PCR); satisfaction level